An Analysis of Person Deixis in 365 Days - Dhanu Ario Putra; Nopriansah Nopriansah; Riski Noprian Thoni; Deni Pratama (Literary Criticism, 2020)
Deixis is an important component of the study of pragmatics and one of its types is person deixis which plays an important role in people's communication. Person deixis is a reference from someone. The use of flexible person deixis can facilitate interpersonal relationships so as to achieve communication goals. The objectives of this study are to identify the types of person deixis that are used in the script Movie Script 365 days, to find out the dominant types of person deixis that are used in the script Movie Script of in 365 days. This research belongs to qualitative research. The researcher uses observation method, while the data collection techniques is listening the song, reading and analyzing the script Movie Script in 365 days. The result of this research show that all types of person deixis are used in the script Movie Script of in 365 days. Person deixis almost occurs in every line of 365 days Movie Script. There are data of person deixis consisting of first-, second-, and third person deixis. Most of personal deixis in 365 days Movie Script refer to the speaker itself which are encoded by first singular person deixis like I and My. While for first plural person deixis which are We mostly refer to the speaker. Keyword: Person Deixis, Movie Script, 365 days